Cluster headache with perimenstrual trigger mimicking chronic migraine: a case report and diagnostic challenge - Gonçalves, Christian (Headache Medicine, 2025)
Introduction Cluster headache (CH) is a trigeminal autonomic cephalalgia known for its excruciating unilateral pain and strong male predominance. Its triggers are rarely hormonal, contrasting with migraine, which is frequently modulated by the menstrual cycle. This discrepancy creates a potential for diagnostic confusion in female patients. Case report A 28-year-old woman presented with a two-year history of excruciating, right-sided periorbital attacks lasting 60-90 minutes. Bouts occurred for 4-6 weeks, exclusively triggered premenstrually. She exhibited prominent psychomotor agitation and ipsilateral autonomic symptoms. Initially diagnosed as refractory menstrual migraine, she was unresponsive to standard migraine treatments. A detailed anamnesis led to a revised diagnosis of episodic CH. Discussion The menstrual trigger, typical of migraine, masked a classic CH presentation, leading to a diagnostic delay. The correct diagnosis was established by focusing on attack phenomenology, particularly the patient’s behavior (agitation vs. rest) and autonomic signs. The patient achieved complete resolution of attacks with high-flow oxygen and verapamil. This case highlights how gender and trigger-related biases can impede correct diagnosis and reinforces the need to consider CH in women with cyclical headaches